Bilateral Macular Edema Complicating Severe Pre-Eclampsia (Global Journal of Medical Research, 2022)
Preeclampsia, is a general syndrome that affects 5% of pregnant women, typically in the last trimester of pregnancy. It is characterized by arterial hypertension associated with proteinuria. A 25-yearold patient, with no notable pathological history, hospitalized for eclampsia and loss of visual acuity. Fundus examination shows diffuse narrowing of the arteries in both eyes, serous retinal detachment with macular retinal folds and stage 1 papilledema. OCT mapping shows retinal disorganization in both eyes inter-papillo-macular with cystoid macular edema, macular thickening and presence of a DSR . At 1 month postpartum, visual acuity was 9/10 in the right eye and 8/10 in the left eye with drying of the macular edema and serous detachment and disappearance of the papilledema.